Child-Friendly School Policy in the Perspective of Islamic Education Teachers in Indonesia - Susanto Susanto (Al Qalam, 2022)
Abstract: Along with some violations of children’s rights in the education unit, the policy of child-friendly schools is a new paradigm for the development of children’s rights-based education units. This study aims to identify the perceptions of Islamic education teachers in the education unit towards child-friendly school policies. This study employed a qualitative approach. The study involved the Islamic education teachers in 3 (three) provinces: DKI Jakarta, West Java and Banten, from August to December 2021. The respondents were the Islamic education teachers of elementary, junior high and high school levels. There were 120 Islamic education teachers. This study took the sample randomly. Moreover, the data were collected through virtual interviews through the zoom platform, distributing questionnaires via google forms and document studies. Then, the data were analyzed descriptively. This study shows that 85% of Islamic education teachers positively view the quality of child-friendly school policies. Furthermore, 72% of teachers view that the content of child-friendly school policies can be extinguished, then 75% of teachers argue that child-friendly school policies are relevant to the need for improving the education service system, then 86% of teachers see that child-friendly school policies have benefits for school culture improvement. Then, 87% of teachers view that it will positively impact the comfort of school personnel. Keywords: Islamic education teachers, Indonesia, child-friendly school policy